2017
DOI: 10.1038/s41598-017-04175-w
|View full text |Cite
|
Sign up to set email alerts
|

Palmitic Acid-BSA enhances Amyloid-β production through GPR40-mediated dual pathways in neuronal cells: Involvement of the Akt/mTOR/HIF-1α and Akt/NF-κB pathways

Abstract: The pathophysiological actions of fatty acids (FAs) on Alzheimer’s disease (AD), which are possibly mediated by genomic effects, are widely known; however, their non-genomic actions remain elusive. The aim of this study was to investigate the non-genomic mechanism of extra-cellular palmitic acid (PA) regulating beta-amyloid peptide (Aβ) production, which may provide a link between obesity and the occurrence of AD. In an obese mouse model, a high-fat diet (HFD) significantly increased the expression levels of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
52
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 82 publications
2
52
0
Order By: Relevance
“…A recent study demonstrated that treatment with exogenous palmitate increases Aβ levels in SK‐N‐MC neuroblastoma cells by activating the G‐protein‐coupled receptor 40/Akt/mammalian target of rapamycin/HIF1α and the G‐protein‐coupled receptor 40/Akt/NF‐κB signaling pathways (Kim et al . ). However, no in vivo study to date has characterized the effects of a palmitate‐enriched diet per se on the transcriptional regulation of BACE1 expression and Aβ genesis and characterized the mechanisms.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…A recent study demonstrated that treatment with exogenous palmitate increases Aβ levels in SK‐N‐MC neuroblastoma cells by activating the G‐protein‐coupled receptor 40/Akt/mammalian target of rapamycin/HIF1α and the G‐protein‐coupled receptor 40/Akt/NF‐κB signaling pathways (Kim et al . ). However, no in vivo study to date has characterized the effects of a palmitate‐enriched diet per se on the transcriptional regulation of BACE1 expression and Aβ genesis and characterized the mechanisms.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, the inference drawn from the aforementioned studies, in the context of enhanced Ab burden in the brain as a consequence of diet, cannot exclusively be ascribed to the saturated fat content, but also to the presence of other macromolecular variables that make-up the constitution of the respective diet. A recent study demonstrated that treatment with exogenous palmitate increases Ab levels in SK-N-MC neuroblastoma cells by activating the G-proteincoupled receptor 40/Akt/mammalian target of rapamycin/ HIF1a and the G-protein-coupled receptor 40/Akt/NF-jB signaling pathways (Kim et al 2017). However, no in vivo study to date has characterized the effects of a palmitateenriched diet per se on the transcriptional regulation of BACE1 expression and Ab genesis and characterized the mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies have shown that SFA augments LPS‐induced proinflammatory gene expression in macrophages and vascular endothelial cells by amplifying TLR4‐mediated inflammatory signaling such as mitogen‐activated protein kinase (MAPK) and nuclear factor kappa B (NFκB) cascades . These findings strongly suggest that free fatty acid receptors such as GPR40 and CD36 are involved in SFA‐enhanced proinflammatory gene expression since SFA engages GPR40 and CD36, which mediate MAPK and NFκB signaling activation . The role of GPR40 and CD36 in the upregulation of proinflammatory cytokine expression was further supported by our findings that inhibition of GPR40 or CD36 attenuated proinflammatory cytokine expression in gingival fibroblasts stimulated by palmitate and LPS (Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that SFA has a higher affinity than unsaturated fatty acid to bind GPR40 . It has been shown that GPR40 mediate palmitate‐enhanced amyloid‐β production by activating inflammatory signaling pathways in neuronal cells . It has been also shown that GPR40 mediated thiazolidinediones‐activated proinflammatory signaling pathways .…”
Section: Discussionmentioning
confidence: 99%